Educational attainment and self-rated health among African-Americans in Pitt County, NC - Eeshwar Chandrasekar; Zimo Banta; Kathleen Ragan; Michelle Schmitz; Sherman James (Georgia Southern University, 2016)
Background: To help fill the knowledge gap regarding relationships between educational attainment and self-rated health (SRH) in minority populations, we analyzed the data of a community-based cohort of African-Americans residing in Pitt County, NC, between 1988 and 2001. Methods: Data from the Pitt County Study (a community-based, longitudinal survey of risk factors for hypertension and related disorders disproportionately affecting African-Americans) were used to explore associations between educational attainment and SRH, stratified by sex, in a cohort of individuals from 1988 (n=1,773), 1993 (n=1,195), and 2001 (n=1,117) using continuous, ordinal, and binary correlated data analyses. Results: For males and females with less than a high school education, the odds of reporting poor or fair health (compared to excellent, very good, or good health) were 2.75 (95% CI: 1.54-4.91) and 1.78 (95% CI: 1.15-2.75) times greater, respectively, than among those who completed a college degree or higher. Conclusions: Across all analyses, individuals with lower educational attainment reported lower SRH scores, and the association differed by sex. Social support may be a factor in these differences. More research is needed, however, to assess relationships between educational attainment, social support, and SRH for African-Americans and other minority populations.